2019
DOI: 10.1002/chem.201806083
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Annulations of N‐Propargyl Ynamides with Anthranils with Two Distinct Chemoselectivities

Abstract: Gold‐catalyzed annulation of N‐propargyl ynamides with anthranils can proceed by two distinct mechanisms. In the case of a terminal N‐propargyl ynamide, its resulting α‐imino gold carbene reacts with a tethered alkyne to generate a vinyl cation to enable hydrolysis, which ultimately yields a pyrrolo[2,3‐b]quinoline derivative after treatment with p‐toluenesulfonic acid. For an internal alkyne, its α‐imino gold carbene reacts with a tethered alkyne via either a vinyl cation or an alkenylgold carbene; both paths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 108 publications
0
8
0
Order By: Relevance
“…The optimized conditions involved the use of (2biphenyl)di-tert-butylphosphine gold chloride ( In a continuous search of viable ynamides in gold-catalyzed nitrene-transfer reactions based on anthranils, Liu and coworkers reported a gold(III)-catalyzed annulation between terminal N-propargyl ynamides 171 and anthranils 172 to construct pyrrolo [2,3-b]quinolines 173 en route to isolable pyrrole species 171-E (Scheme 80). 97 In a standard catalytic operation, terminal ynamides 171 and anthranils 172 were initially treated with AuCl 3 (5 mol %) until a complete consumption of ynamide, before treating this AuCl 3 -catalyzed reaction with TsOH (20 mol %) to ensure complete conversion of pyrrole 171-E to pyrrolo[2,3-b]quinolines 173. This catalytic system was employed to construct pyrroloquinoline cores from various electron-rich and -deficient N-propargyl ynamides and anthranils.…”
Section: Gold-catalyzed Nitrene-transfer Reactions Based On Anthranilsmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimized conditions involved the use of (2biphenyl)di-tert-butylphosphine gold chloride ( In a continuous search of viable ynamides in gold-catalyzed nitrene-transfer reactions based on anthranils, Liu and coworkers reported a gold(III)-catalyzed annulation between terminal N-propargyl ynamides 171 and anthranils 172 to construct pyrrolo [2,3-b]quinolines 173 en route to isolable pyrrole species 171-E (Scheme 80). 97 In a standard catalytic operation, terminal ynamides 171 and anthranils 172 were initially treated with AuCl 3 (5 mol %) until a complete consumption of ynamide, before treating this AuCl 3 -catalyzed reaction with TsOH (20 mol %) to ensure complete conversion of pyrrole 171-E to pyrrolo[2,3-b]quinolines 173. This catalytic system was employed to construct pyrroloquinoline cores from various electron-rich and -deficient N-propargyl ynamides and anthranils.…”
Section: Gold-catalyzed Nitrene-transfer Reactions Based On Anthranilsmentioning
confidence: 99%
“…In contrast, a distinct chemoselectivity was observed in the case of internal N -propargyl ynamides 174 in the gold­(III)-catalyzed annulation with anthranils 172 , giving a mixture of imine derivative 175 and hydrolyzed pyrrole product 176 , which on further treatment with HCl (37%, 1 equiv) gave hydrolyzed pyrrole 176 as a sole product (Scheme ). On the basis of a mechanistic analysis, water and anthranil were found to be equally reactive in the second nucleophilic attack, generating two distinct products at the initial stage. Various substituents on both N -propargyl ynamides and anthranils were tolerated to yield the corresponding pyrrole products.…”
Section: Gold-catalyzed Nitrene-transfer Reactions Based On Isoxazole...mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the presence of a cation-stabilizing group or the highly nucleophilic nature of alkynes, the electrophilic character of the initially formed gold carbene could also be an important factor in controlling the mechanistic premise of these reactions. Along these lines, recently Liu and co-workers (Scheme 13) [31] reported that a donor-acceptor type of gold carbene 60 generated from a gold-catalyzed reaction of anthranil 57 with an aryl-substituted alkyne would favour a [1,n]-carbene transfer process to afford 62 (by Path A, C or D) whereas a more electrophilic acceptor-gold carbene generated from gold-catalyzed reaction of anthranil with a terminal alkyne would favor a mechanism with Path B (cf. 61).…”
Section: Scheme 10mentioning
confidence: 94%
“…quinolone derivatives were obtained in one-pot under mild reaction conditions (Scheme 44). 60 A tentative mechanism for this transformation was proposed. Initially, the α-imino gold carbene complex 119a was generated through the abovementioned process, and was attacked by a tethered internal alkyne to generate the alkenyl cation 119b.…”
Section: Formal [4 + 2] Cycloaddition Of Anthranilsmentioning
confidence: 99%